PROJECT METHOD IN THE SYSTEM OF CONTROL OF EDUCATIONAL ACHIEVEMENTS OF STUDENTS OF PEDAGOGICAL UNIVERSITY - I. V. Panova (Вестник Мининского университета, 2017)
The article discusses the possibility of using project method in the process of teaching different sections of substantive and methodological training of bachelors of pedagogical education profile "Informatics". The author analyzes the essence of project method in historical perspective, in the context of schooling and in relation to the system of higher professional education. The options considered to use a method of projects as a form of intermediate and final attestation for the subjects and methodological training of future teachers of Informatics. Presents the wording of the tasks for design work, identify indicators and scale of the evaluation project works of students on disciplines of "Information systems" and "Methods of teaching Informatics". Recommendations on the use of the item "seminar" in Moodle LMS as a means for joint assessment of project work.